Cost-effectiveness of biofire assay for respiratory infection testing: An economic evaluation exploring the inclusion of the costs of antimirobial resistance - Raymond Oppong; Raj Gill; Kay Roy (PLoS ONE, 2026)
Background Patients diagnosed with chronic obstructive pulmonary disease (COPD) often face acute symptom exacerbations. Current management approaches lack precision in diagnosis. To address this, the Biofire Film Array Respiratory Panel RP 2.1 (RP 2.1+) test was developed, aiming to swiftly confirm or rule out common respiratory viral and bacterial infections. This study aims to evaluate the RP 2.1 + test’s cost-effectiveness and explore the potential impact of accounting for the costs of antimicrobial resistance. Methods We conducted a model-based cost-utility analysis from a healthcare perspective over 40 years. The design of our model, along with its parameters, was informed by insights from a targeted literature review and expert opinions. To account for antimicrobial resistance (AMR) two approaches were adopted. Including applying penalty points to the cost of antibiotic prescriptions and estimating the potential cost savings from reductions in AMR. Results The results indicate that the RP 2.1 + test is cost-saving and more effective. The difference in costs and QALYs between arms were £2762.40 and 0.03 respectively and there is a 70% chance that the RP 2.1 + test is cost-effective. The analysis suggest that potential annual savings from adopting the RP 2.1 + test could range between £118 million and £18.6 billion annually. Conclusion The RP 2.1 + test represents a cost-effective use of healthcare resources and would lead to significant savings with respect to AMR. The study has attempted to account for AMR within the economic evaluation and has highlighted areas where further research is needed to account for AMR more precisely in future evaluations.